Sustainable urban ecosystems and quality of life: achievements in European countries - Roderick J. Lawrence (Environmental Management Society, Malaysia, 2010)
Urbanization produces profound transformations of human and natural ecosystems which have not been well understood in terms of both positive and negative impacts. The interrelations between urban planning, health, social, economic and environmental policies have been poorly articulated until recently. Since the 1990s, and in conjunction with policies and programmes implementing sustainable development, several innovative initiatives have been implemented. These include the Aalborg Charter in 1994 leading to the Sustainable Cities and Towns Campaign, the Aarhus Convention in 1998, and the Aalborg Commitments in 1998. These initiatives and achievements are summarized in this paper